Intervention to Enhance Successful Aging: Literature Review for the Eldery - Mumtaz Afridah (UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to analyze the appropriate interventions to increase successful aging in the elderly and the factors that affect it. Successful aging is a concept that includes physical, mental, and social well-being of the elderly. At this time there is a gap between increasing the life expectancy of the elderly and the happiness and welfare of the elderly. This shows the need for a comprehensive treatment for the elderly as a reference for the treatment of the elderly in filling their old age. The research method used is a qualitative method with literature study. Literature study is research that has a role to outline the main concepts and relevant previous findings, as well as to identify the development of research in a topic. The research results show that there are various interventions based on factors that can affect successful aging, including social dimension factors, physical dimension factors, psychological dimension factors, spiritual dimension factors.